2017
DOI: 10.2217/ijh-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Untreated Chronic Lymphocytic Leukemia in Lebanese Patients: An Observational Study Using Standard Karyotyping and FISH

Abstract: Background • The chronic lymphocytic leukemia (CLL) pathogenesis shows a molecularly variable disease with particular cytogenetic characteristics that constitute nowadays the major prognostic factors. • The epidemiology of CLL in the Middle Eastern population has not been fully studied. • The modeling of the CLL epidemiology at the population level is required to personalize the treatment plan at the individual level. Patients & methods • All the newly diagnosed CLL patients who did not require treatment were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…In contrast to Western countries, the Middle Eastern population tends to be younger, potentially with a different profile of comorbidities [ 10 , 11 ]. Comorbidities have been shown to impact survival outcomes in patients with CLL [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Western countries, the Middle Eastern population tends to be younger, potentially with a different profile of comorbidities [ 10 , 11 ]. Comorbidities have been shown to impact survival outcomes in patients with CLL [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A national Danish CLL registry study then confirmed the ability of CLL-CI to predict time to first treatment (TTFT), EFS, and overall survival (OS), with the latter two outcomes measured from both diagnosis and first treatment [ 9 ]. The Middle Eastern CLL population, however, is much younger (median age at CLL diagnosis of 59 years) than in the West (median age of 70 years) and has a different comorbidity profile [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to Western cohorts, the Middle Eastern population tends to be younger and has different genetic profile [ 19 , 20 ]. This raises potential implications for the validity of widely used prognostic scores originally developed in the West.…”
Section: Discussionmentioning
confidence: 99%
“…The Middle East has a notably younger CLL population, with a median age at diagnosis of 59 years, compared to 70 in Western populations [18][19][20]. Furthermore, there are some genetic differences between Middle Eastern and Western CLL patients [19].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of CLL is still elusive, however, it is most likely that genetics and environmental factors have an important effect on its occurrence [4][5]. In the karyotype experiments, del13q14, trisomy 12, del11q22-q23, and del17p13 were associated with CLL [6]. Several other molecular pathologies were found in CLL, such as the overexpression of the unmutated immunoglobulin heavy chain variable region (IGHV) genes, zeta-chainassociated protein kinase 70 (ZAP-70), CD38 proteins, and mutations in the NOTCH1, splicing factor 3b subunit 1 (SF3B1), and baculoviral IAP repeat-containing 3 (BIRC3) genes.…”
Section: Introductionmentioning
confidence: 99%